2003
DOI: 10.1002/j.1839-4655.2003.tb01159.x
|View full text |Cite
|
Sign up to set email alerts
|

From Here to Maternity: A Review of the Research on Lesbian and Gay Families

Abstract: is a Senior Lecturer in Law at the University of Sydney. Over the past 10 years she has researched extensively into lesbian and gay family law and relationship recognition in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 20 publications
(5 reference statements)
0
43
0
1
Order By: Relevance
“…There is a distinct lack of information about how same-sex families are formed and how they function (Millbank 2003). Most of the studies regarding same-sex couples have focused on the legal aspect of the phenomenon and on the public discourse about it (Brandzel 2005;Cahill 2005;Rollins 2005; Rosenfeld and Kim 2005).…”
mentioning
confidence: 99%
“…There is a distinct lack of information about how same-sex families are formed and how they function (Millbank 2003). Most of the studies regarding same-sex couples have focused on the legal aspect of the phenomenon and on the public discourse about it (Brandzel 2005;Cahill 2005;Rollins 2005; Rosenfeld and Kim 2005).…”
mentioning
confidence: 99%
“…Despite these challenges, and in contrast to the assumptions and stereotypes that tend to be associated with gay male, lesbian and bisexual parents, there are no reported significant differences in a range of areas between children of same-sex parents and those raised in more traditional heterosexual parented families (Milbank, 2003), thus highlighting the resilience of this group. The current study sought to investigate these non-traditional families and the dynamics underpinning their resilience.…”
Section: Resilience In Same-sex Parented Familiesmentioning
confidence: 85%
“…Challenges Specific to Same-sex Parented Families Much of the policy and public perception of the adequacy of parenting in same-sex headed families is based on the premise that it is problematic and less than ideal for children (Milbank, 2003). Evidence of this specific discrimination against gay parents can be seen in a 1995 study by Fraser, Fish and Mackenzie.…”
Section: Legal and Political Challengesmentioning
confidence: 99%
“…Crowl, Ahn and Baker (2008) ascribed this to the fact that (after divorce) lesbian mothers more frequently require custody of children than fathers. Jenni Millbank (2003), however, thought that this is also the result of lesbian couples more frequently desiring a child than gay couples; as a consequence, they more frequently opt for artificial insemination or adoption. Stacey and Biblarz (2001) believed that the methodological problems in thisarea of study arose predominantly because "… so many individuals legitimately fear the social consequences of adopting a gay identity, and because few national surveys have included questions about sexual orientation, it is impossible to gather reliable data on such a basic demographic question as how many lesbians and gay men there are in the general population, how many have children, or how many children reside (or have substantial contact) with lesbian or gay parents" (2001: 164).…”
Section: The Methodsological Deficiencies Of the Research Studiesmentioning
confidence: 99%
“…Moreover, Millbank (2003) pointed out that "Someresearch suggests that lesbian and gay families are in some respects better for children than heterosexual families … Research on the division of parenting and household labour among lesbian co-parents and gay-co-parents has shown a distinct pattern of equality and sharing compared to heterosexual parents, with corresponding positive wellbeing for the partner's relationship with each other, and the child's adjustment" (Millbank, 2003: 546-547). Research studies show that "… gay and lesbian parents tend to be more responsive to their children, more child oriented, and more egalitarian in their sharing of the workload, characteristics associated with a more positive child outcome" (Johnson & O'Connor, 2002: 67).The study carried out by Rachel H. Farr, Stephen L. Forssell and Charlotte J. Patterson (2010) comparing homosexual and heterosexual families with adopted children showed that the processes within the family outweigh the family's structure.…”
Section: How Does Growing Up In Rainbow Families Affect Children Andmentioning
confidence: 99%